Preparation method of cyclodextrin polymer loaded hydrotalcite material for efficiently activating persulfate

CN117920147BActive Publication Date: 2026-10-27INSTITUTE OF MICROBIOLOGY JIANGXI ACADEMY OF SCIENCES (JIANGXI INSTITUTE OF WATERSHED ECOLOGY)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410080969.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-19
Publication Date
2026-10-27
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

[0006]本发明所要解决的问题是制备一种新型的CDP-LDH复合材料用以高效去除水体有机污染物

Benefits of technology

[0021]本发明的有益效果:本发明主要针对CDP材料不能够催化氧化剂降解有机物污染物,而LDH材料没有选择性吸附有机物污染物的效能。巧妙地将二者以交联聚合的方法掺杂在一起,克服各自在有机物污染修复方面的缺点。在天然水体中,由于CDP的引入,有效减少了LDH催化剂在应用过程中受到天然有机物、铵根离子及其他杂质离子的影响。本发明可以通过调控LDH变价元素的电子转移和层间碱度加速对过硫酸盐的高效活化能力,同时环糊精对污染物的包合作用增加了难降解污染物的传质能力,在处理实际污染水体时可以多次重复使用,对大多数有机污染物的去处效果可达到90%以上。材料的制备过程简单实用,原料经济可行,具有一定的应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920147B_ABST
    Figure CN117920147B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of water organic pollutant purification, and discloses a preparation method of a cyclodextrin polymer supported hydrotalcite material for efficiently activating persulfate. The CDP material is ingeniously combined with the LDH, so that the rigidity of the CDP material itself is increased and the CDP material has catalytic performance. In the crosslinking polymerization reaction process of the cyclodextrin-epichlorohydrin, the LDH is added, so that the LDH is inlaid in the CDP network structure. The prepared CDP-LDH composite material still has high adsorption performance on organic pollutants such as benzene series, and can also activate persulfate to generate active free radicals to increase the removal effect of the organic pollutants. The method is simple in operation, the prepared material is stable in performance, and has certain application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water body organic pollutant degradation and purification technology, specifically involving a method for preparing cyclodextrin polymer material (CDP) based on layered bimetallic hydroxide (LDH) modification and its application in the degradation and purification of organic pollutants such as benzene series compounds in water bodies. Background Technology

[0002] The persulfate advanced oxidation process is widely used for the degradation and purification of organic pollutants in water bodies due to its low cost, ease of long-distance transportation, and environmental friendliness. It accelerates the production of H₂O· and SO₄²⁻ from persulfate through activation methods such as alkali, heat, transition metals, and organic carbon. ·- This technology can enhance the rapid and efficient degradation of pollutants. Developing catalytic materials with high efficiency and long-lasting activation properties for persulfate is a prerequisite for its large-scale practical application.

[0003] LDH is a typical anionic two-dimensional clay mineral, mainly composed of cationic lamellar structures and interlayer anions. The divalent ions in LDH with catalytic properties mainly include variable-valence metals such as Co, Fe, Zn, Mn, and Ni, which not only possess the traditional interlayer basicity of LDH but also have strong electron transfer capabilities. The activation performance of LDH can be effectively improved through interlayer modification and surface hybridization. For example, inserting substances with homogeneous catalytic activity, such as inorganic anions, organic acids / bases, and organic complexes, into the LDH interlayer can transform homogeneous catalysis into heterogeneous catalysis. Patent CN202210301552.0 developed a triammonium citrate-modified trace cobalt-doped magnesium-aluminum ternary layered double hydroxide composite catalyst, which has advantages such as low leaching risk, high catalytic activity, and good recyclability. Patent CN201610439211.4 discloses a method for preparing tetraaminoiron ligand-intercalated LDH, which can efficiently catalyze the degradation of tetrabromobisphenol A by hydrogen peroxide and can be reused multiple times. Although LDH can adsorb most anionic organic pollutants and catalyze the degradation of organic pollutants by activated oxidants, its hydrophilic surface and the hydrophobic surface of organic matter repel each other, which seriously hinders the mass transfer of organic matter to the LDH surface or between layers. Therefore, the removal effect on most non-anionic organic matter is not ideal.

[0004] Cyclodextrin polymers (CDPs) are heterogeneous network macromolecular polymers composed of different cyclodextrin (CD) monomers linked by chemical bonds. Inheriting the supramolecular recognition ability of CD monomers, they can efficiently adsorb organic pollutants in water through inclusion interactions between host and guest molecules. Assembling materials with redox and catalytic activation properties with CDPs can produce multifunctional composite materials. Patent CN202110223649.X discloses a method for controllable preparation of carbon-supported metal single-atom catalysts based on cyclodextrin supramolecular chemistry, employing a cyclodextrin supramolecular self-assembly confined pyrolysis method to encapsulate catalytically active metal precursors within the supramolecular cavities of cyclodextrins. Patent CN202011422772.6 discloses a method for preparing and applying a tetraaminoiron ligand catalyst-magnesium oxide-cyclodextrin composite material. This composite material contains the highly reactive Fe-TAML and MgO to maintain the alkaline environment required for the Fe-TAML / H2O2 system, making the catalytic activity of Fe-TAML on H2O2 unaffected by pH. Furthermore, this material can achieve 100% degradation of clofenac even after three cycles of H2O2 activation within a pH range of 3–9. Patent CN202110278673.3 discloses a method for preparing and applying a selectively adsorbed spherical zero-valent iron-cyclodextrin composite material. Reducible nano-zero-valent iron is uniformly coated in CDP, slowing down the aggregation and oxidation of zero-valent iron nanoparticles, which is beneficial for the selective and efficient reduction and removal of pollutants such as nitrobenzene, and is less affected by environmental components.

[0005] Given that CDP materials exhibit selective adsorption but lack catalytic properties, while LDH possesses catalytic activity but lacks selective adsorption, this paper considers combining the advantages of both to prepare a novel composite material that possesses both excellent selective adsorption properties and maintains high catalytic activity. Summary of the Invention

[0006] The problem this invention aims to solve is to prepare a novel CDP-LDH composite material for the efficient removal of organic pollutants from water. By cleverly combining CDP material with LDH, both the rigidity of the CDP material and its catalytic efficiency are increased. LDH is added during the cyclodextrin-epoxychloropropane crosslinking polymerization reaction, allowing LDH to be embedded in the CDP network structure. This ensures that the CDP material retains its high adsorption capacity for organic pollutants such as benzene compounds. This method is simple to operate, and the prepared material exhibits stable properties and has certain application value.

[0007] The technical solution of the present invention:

[0008] A method for preparing a hydrotalcite material supported on a cyclodextrin polymer with high efficiency in activating persulfate, comprising the following steps:

[0009] (1) Preparation of LDH material: Weigh out divalent and trivalent metal salts and dissolve them in ultrapure water to obtain a solution A with a concentration of 0.1-4.0 mol / L, wherein the molar ratio of divalent metal to trivalent metal is 2:1 to 3:1; prepare an alkaline solution B with a concentration of 0.5-5 mol / L, slowly mix the same volume of solution A and alkaline solution B, and stir continuously to mix thoroughly, keeping the pH between 9 and 10. Place the completely mixed suspension in a high-pressure reactor and perform a hydrothermal reaction at 50-150℃ for 5-24 hours.

[0010] LDH materials are LDH materials containing variable valence metal ions, such as: MnFe-LDH, NiFe-LDH, ZnFe-LDH, ZnTi-LDH, NiMgAl-LDH, CuFe-LDH and MnFe-LDH.

[0011] Alkaline solution B is a strong alkaline solution (such as sodium hydroxide, potassium hydroxide, ammonia, etc.), which decomposes urea upon heating or induces urea to produce alkali through microbial induction.

[0012] (2) Preliminary cross-linking of cyclodextrin and LDH: Dissolve cyclodextrin in sodium hydroxide solution, sonicate to completely dissolve, add LDH material and mechanically stir for 4-6 h, control the temperature at 30-40℃, slowly add cross-linking agent epichlorohydrin at a rate of 0.5-2 mL / min, stir at a speed of 350-400 rpm, react for 1-2 hours to obtain a preliminary cross-linking system of cyclodextrin and LDH;

[0013] Among them, cyclodextrin is one or more of α-CD, β-CD, γ-CD, and HPCD;

[0014] The mass ratio of cyclodextrin to LDH is 3.3:1 to 50:1;

[0015] The mass ratio of cyclodextrin to epichlorohydrin is 2:1 to 4:1.

[0016] (3) CDP-LDH gel formation: The cyclodextrin and LDH preliminary cross-linking system was heated to 50°C, the rotation speed was adjusted to 550-700 rpm, an alkaline solution with a saturation of 40% was added, and a n-decane solution containing a dispersant was quickly added and emulsified for 30 min; then the temperature was raised to 60°C, epichlorohydrin was added, and the reaction was maintained at 550-700 rpm for 30 min, then the rotation speed was reduced to 500 rpm, and epichlorohydrin was added every 30 min until a significant solid gel was formed, and the reaction was continued for another 30 min; the obtained solid complex was washed three times with ethanol and ultrapure water respectively, the supernatant was removed, and the mixture was placed in a freeze dryer for drying.

[0017] The mass ratio of cyclodextrin to alkaline solution is 2:1 to 3:1.

[0018] The dispersants are span80 and tween20, with a mass ratio of 2:1 to 4:1, and the mass of the dispersants accounts for 2% of the total mass of the n-decane solution.

[0019] The mass ratio of cyclodextrin to n-decane is 1:3;

[0020] The total mass of epichlorohydrin added in two additions depends on the amount of LDH added. When the mass ratio of LDH to CD is ≤1:10, the mass ratio of epichlorohydrin to CD is 1:1 to 1.6:1. When the mass ratio of LDH to CD is 1:10 to 1:3.3, the mass ratio of epichlorohydrin to CD is 2:1 to 3:1.

[0021] The beneficial effects of this invention are as follows: This invention primarily addresses the shortcomings of CDP materials in catalyzing the degradation of organic pollutants by oxidants, and LDH materials in selectively adsorbing organic pollutants. By cleverly combining the two through cross-linking polymerization, the individual limitations in organic pollution remediation are overcome. In natural water bodies, the introduction of CDP effectively reduces the impact of natural organic matter, ammonium ions, and other impurity ions on the LDH catalyst during application. This invention can accelerate the efficient activation of persulfate by regulating the electron transfer of variable valence elements and interlayer basicity in LDH. Simultaneously, the inclusion effect of cyclodextrin on pollutants increases the mass transfer capacity of recalcitrant pollutants. It can be reused multiple times in treating actual polluted water bodies, achieving a removal efficiency of over 90% for most organic pollutants. The preparation process is simple and practical, the raw materials are economical and feasible, and it has considerable application potential. Attached Figure Description

[0022] Figure 1 This is a kinetic diagram of the degradation of benzene in water by persulfate activated by CDP-MnFeLDH composite material.

[0023] Figure 2 This is a kinetic diagram of the degradation of toluene in water by CDP-MnFeLDH composite material activated by persulfate.

[0024] Figure 3 The CDP-NiFeLDH composite material is activated by the cyclic degradation of sulfate to simulate atrazine in groundwater.

[0025] Figure 4 It is DOM and HCO3 - The effect of CDP-NiFeLDH / PMS on the oxidative degradation of atrazine, where a represents the effect of DOM on the oxidative degradation of atrazine by CDP-NiFeLDH / PMS, and b represents the effect of HCO3-. - The effect of CDP-NiFeLDH / PMS on the oxidative degradation of atrazine. Detailed Implementation

[0026] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0027] Example 1: Preparation of CDP-MnFeLDH Composite Material

[0028] 53.7 mL of manganese nitrate (50% by mass) and 60.6 g of ferric nitrate nonahydrate were mixed and dissolved in 300 mL of ultrapure water, labeled as solution A. 30 g of sodium hydroxide and 15.9 g of sodium carbonate were dissolved in 300 mL of ultrapure water and mixed to prepare solution B. Solutions A and B were slowly mixed at a rate of 2 mL / min. After complete addition, the mixture was allowed to react at room temperature for 1 hour. Then, it was placed in a high-pressure reactor and hydrothermally reacted at 80 °C for 12 hours. After cooling, solid-liquid separation was performed at 5000 rpm, followed by freeze-drying to obtain MnFeLDH material.

[0029] Weigh 17.6g of sodium hydroxide and dissolve it in 100mL of ultrapure water. Dissolve 50g of cyclodextrin completely in the sodium hydroxide solution using ultrasonication. Add 2.5g of LDH and react at room temperature for 1 hour. Heat to 30℃ and slowly add 30g of epichlorohydrin at a rate of 1mL / min, reacting for 1 hour. Heat to 50℃ and add 22mL of 40% sodium hydroxide solution and 150mL of n-decane (containing 3g of dispersant, with a Span 80 and Tween 20 mass ratio of 3:1). Stir at 600 rpm for 30 minutes. Heat to 60℃, adjust the stirring speed to 500 rpm, and maintain this temperature for 30 minutes. Add 20g of epichlorohydrin and continue to maintain the temperature until gel formation occurs. Wash three times with ethanol and ultrapure water, separate the solid and liquid phases, and freeze-dry to obtain the desired composite material. When the amount of LDH added was 5.0 g and 10.0 g, the amount of epichlorohydrin added was 80 g and 120 g, respectively. Three different composite materials were prepared, all retaining the amorphous structure of CDP and the crystalline structure of LDH.

[0030] Example 2: Preparation of CDP-NiMgAlLDH Composite Material

[0031] Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, Al(NO3)3·9H2O, and urea were simultaneously added to 200 mL of deionized water. The metal cation Ni... 2+ Mg 2+ And Al 3+ The feed molar ratio to urea is 3. The total feed amount of metal cations is 40 mmol, of which the molar amount of divalent metal cations is 30 mmol, Ni 2+ / Mg 2+The molar ratio was 2:1. The mixture was ultrasonically dissolved for 30 min, then transferred to a 100 mL Teflon-lined reactor, which was placed in a stainless steel autoclave. The reaction was carried out hydrothermally at 120 °C for 6 h. The resulting green colloid was washed several times with deionized water and ethanol to remove excess ions, and the solid material was collected by centrifugation. The solid was then dried in an oven at 70 °C for 10 h to obtain NiMgAl LDH powder.

[0032] Weigh 5 g of sodium hydroxide and 16.5 g of β-cyclodextrin and add them to 100 mL of ultrapure water. Dissolve by sonication for 30 min. Add 3.3 g of LDH and react with magnetic stirring at 200 rpm for 1 hour. Heat to 40 °C and slowly add 10 g of epichlorohydrin at 2 mL / min. Stir mechanically at 400 rpm for 2 hours. Heat to 50 °C and add 8 mL of 40% sodium hydroxide solution and 100 mL of n-decane (containing 2 g of dispersant, with a Span 80 and Tween 20 mass ratio of 3:1). Stir at 600 rpm for 30 min. Heat to 60 °C, adjust the stirring speed to 500 rpm, and hold for 30 min. Add 30 g of epichlorohydrin and continue holding until gel formation. Wash three times with ethanol and ultrapure water, separate the solid and liquid phases, and freeze-dry to obtain the CDP-NiMgAlLDH composite material.

[0033] Example 3: Degradation of benzene series compounds in water using a CDP-MnFeLDH / PMS oxidation system

[0034] Batch experiments on the degradation of benzene compounds by CDP-MnFeLDH / PMS were conducted in 40 mL amber glass vials. CDP and CDP-LDH were used in the experiments. 2.5 CDP-LDH 5.0 CDP-LDH 10 Four adsorption systems and the PMS oxidation system alone served as control groups, with CDP-LDH set up as a control. 2.5 / PMS, CDP-LDH 5.0 / PMS, CDP-LDH 10The three oxidation systems of PMS served as the experimental groups. All reaction solutions were 30 mL, containing 10 mg / L of benzene compounds. The amount of PS in the oxidation system was set to 10 mmol / L, and the amount of solid catalyst added was 0.3 g. All experiments were performed in triplicate. At specific time intervals, 1 mL of reaction solution was drawn using a disposable syringe, filtered through a 0.22 μm polyethersulfone membrane, and 200 μL of ethanol was immediately added to the filtrate to terminate the reaction. The concentration of benzene compounds was then determined using high-performance liquid chromatography (HPLC). After 90 min of reaction, the removal efficiency of benzene by PMS was only 13%, while the adsorption of benzene by CDP and its composite materials reached 56%–66%, and the degradation efficiency of benzene by the CDP-LDH / PMS oxidation system was as high as 75%–82% (see appendix). Figure 1 PMS achieves a benzene removal efficiency of only 23%, while CDP and its composites achieve an adsorption rate of 66%–75% for toluene. The CDP-LDH / PMS oxidation system, however, achieves a toluene degradation efficiency as high as 78%–95% (see appendix). Figure 2 This indicates that CDP-LDH can significantly activate PMS to efficiently degrade benzene compounds in water.

[0035] Example 4: CDP-NiFeLDH 5.0 Catalytic degradation of atrazine by PMS in simulated water bodies

[0036] CDP-NiFeLDH was prepared according to Example 1. 5.0 Catalytic materials, research on CDP-NiFeLDH 5.0 Application of PMS in simulated groundwater bodies. Cl in simulated water bodies. -1 Na + HCO3 - SO4 2- Ca 2+ The concentrations of HA were 234 mg / L, 230 mg / L, 183 mg / L, 96 mg / L, 32 mg / L, and 2 mg / L, respectively, and the concentration of atrazine was 10 mg / L. 2.0 g / L of CDP-NiFeLDH catalyst and 5.0 mmol / L potassium persulfate (PMS) were added to the reaction system, and the reaction was carried out in a constant temperature and rate apparatus for 120 min. After filtration and quenching, the pollutant concentration was detected by high performance liquid chromatography. The solid material after the reaction was centrifuged to separate the solid and liquid phases, and then added back into the polluted simulated water body. PMS was added for oxidative degradation, and this process was repeated 5 times. The results showed that after 5 cycles, CDP-NiFeLDH... 5.0 / PMS can still achieve a degradation rate of over 90% for atrazine.

[0037] Example 5: DOM and HCO3 - CDP-NiFeLDH5.0 The impact of PMS on atrazine degradation in water bodies

[0038] DOM and HCO3 at different concentrations - CDP-NiFeLDH was carried out in solution. 5.0 Oxidative degradation experiments of atrazine using PMS were conducted. The concentration of DOM was set at 2-10 mg / L, and HCO3- was... - The concentration was set at 10-500 mg / L, and the atrazine concentration was 10 mg / L. 2.0 g / L CDP-NiFeLDH catalyst and 5.0 mmol / L PMS were added to the reaction system, and the reaction was carried out in a constant temperature and rate apparatus for 120 min. After filtration and ethanol quenching, the pollutant concentration was detected by high-performance liquid chromatography (HPLC). The results showed that DOM and HCO3- - The oxidative degradation activity of CDP-NiFeLDH / PMS was minimally affected, even at 10 mg / L DOM and 500 mg / L HCO3. - Despite the influence of [the specific technology / effect], CDP-NiFeLDH / PMS can still achieve a degradation rate of over 90% for atrazine.

Claims

1. A method for preparing a hydrotalcite material supported on a cyclodextrin polymer with high efficiency activated persulfate, characterized in that, The steps are as follows: (1) Preparation of LDH material: Weigh out divalent metal salt and trivalent metal salt and dissolve them in ultrapure water to obtain solution A with a concentration of 0.1-4.0 mol / L, wherein the molar ratio of divalent metal to trivalent metal is 2:1~3:1; prepare alkaline solution B with a concentration of 0.5-5 mol / L, slowly mix the same volume of solution A and alkaline solution B, and stir continuously to mix thoroughly, keeping the pH between 9 and 10. Place the completely mixed suspension in a high-pressure reactor and perform hydrothermal reaction at 50-150℃ for 5-24 hours. (2) Preliminary cross-linking of cyclodextrin and LDH: Dissolve cyclodextrin in sodium hydroxide solution, sonicate to completely dissolve, add LDH material and mechanically stir for 4-6 h, control the temperature at 30-40℃, slowly add cross-linking agent epichlorohydrin at a rate of 0.5-2 mL / min, stir at a speed of 350-400 rpm, react for 1-2 hours to obtain the preliminary cross-linking system of cyclodextrin and LDH; (3) CDP-LDH gel formation: The cyclodextrin and LDH preliminary cross-linking system was heated to 50°C, the rotation speed was adjusted to 550~700 rpm, an alkaline solution with a saturation of 40% was added, and a n-decane solution containing a dispersant was quickly added and emulsified for 30 min; then the temperature was raised to 60°C, epichlorohydrin was added, and the speed was maintained at 550~700 rpm for 30 min, then the rotation speed was reduced to 500 rpm, and epichlorohydrin was added every 30 min until obvious solid gel was formed, and the reaction was continued for another 30 min; the obtained solid complex was washed three times with ethanol and ultrapure water respectively, the supernatant was removed, and it was placed in a freeze dryer for drying.

2. The method for preparing highly efficient activated persulfate cyclodextrin polymer-supported hydrotalcite material according to claim 1, characterized in that, In step (1), LDH materials are LDH materials containing variable valence metal ions; Alkaline solution B is a strong alkaline solution, formed by heating urea to decompose it or by microbial induction of urea to produce alkali.

3. The method for preparing highly efficient activated persulfate cyclodextrin polymer-supported hydrotalcite material according to claim 1, characterized in that, In step (2) Cyclodextrin is one or a mixture of two or more of α-CD, β-CD, γ-CD, and HPCD; The mass ratio of cyclodextrin to LDH is 3.3:1 to 50:1; The mass ratio of cyclodextrin to epichlorohydrin is 2:1 to 4:

1.

4. The method for preparing highly efficient activated persulfate cyclodextrin polymer-supported hydrotalcite material according to claim 1, characterized in that, In step (3) The mass ratio of cyclodextrin to alkaline solution is 2:1 to 3:1; The dispersants are Span80 and Tween20, with a mass ratio of 2:1 to 4:1, and the mass of the dispersants accounts for 2% of the total mass of the n-decane solution. The mass ratio of cyclodextrin to n-decane is 1:3; The total mass of epichlorohydrin added depends on the amount of LDH added. When the mass ratio of LDH to cyclodextrin is ≤1:10, the mass ratio of epichlorohydrin to cyclodextrin is 1:1~1.6:

1. When the mass ratio of LDH to cyclodextrin is 1:10~1:3.3, the mass ratio of epichlorohydrin to cyclodextrin is 2:1~3:1.

Citation Information

Patent Citations

  • Composite capable of efficiently degrading tetrabromobisphenol A, as well as preparation method and application method of composite

    CN106111204A

  • Preparation method and application of tetramino iron ligand catalyst-magnesium oxide-cyclodextrin composite material

    CN112657556A

  • Controllable carbon-supported metal monatomic catalyst prepared based on cyclodextrin supramolecular chemistry and preparation method and application method of controllable carbon-supported metal monatomic catalyst

    CN112871150A

  • Preparation method and application of spherical zero-valent iron-cyclodextrin composite material with selective adsorption

    CN113019344A

  • Triammonium citrate modified trace cobalt-doped magnesium-aluminum ternary hydrotalcite-like composite catalyst as well as preparation method and application thereof

    CN114832826A